Patient Satisfaction and Symptoms Improvement in Women Using a Vginal Pessary for The Treatment of Pelvic Organ Prolapse - Radnia, Nahid (J Med Life, 2019)
Pelvic organ prolapse is a common complaint among older women. Vaginal pessary insertion is an appropriate treatment as a non-surgical method with few complications. This paper is a prospective observational study of 68 patients with pelvic organ prolapse that was carried out at the Imam Khomeini Hospital’s Pelvic Floor clinic. The degree of pelvic organ prolapse was graded according to the Pelvic Organ Prolapse Quantification (POP-Q) System. For all patients, the Pelvic Floor Distress Inventory-20 (PFDI-20) questionnaire was completed before vaginal pessary insertion, and after approximately 6 months of treatment. After 6-8 months, we found out that vaginal discharge was significantly increased and the feeling of fullness in the vagina was significantly decreased. However, sexual dissatisfaction, the feeling of incomplete evacuation, fecal and urinary incontinence, frequent urination, and pain or discomfort in the genital region were not significantly different after using a pessary. Approximately half a year later, 96.7% of the women with a successful pessary fitting trial were satisfied and reported a significant improvement in symptoms. Further studies with larger sample size, a different type of pessary, and a longer follow-up duration are recommended to evaluate all the symptoms associated with pelvic organ prolapse and its treatment.